# (electricity) How do I solve for A,B,C when: (1)-2A+B-3C=-9 (2)2A -C=-1 (3)A- B + 4C =11

*print*Print*list*Cite

Student Comments

aruv | Student

We have

`-2A+B-3C=-9` (i)

`2A-C=-1` (ii)

`A-B+4C=11` (iii)

adding (i) and (ii),we have

`B-4C=-10` (iv)

adding 2times (iii) to (i),we have

`-B+5C=13` (v)

adding (iv) and (v) ,we have

`C=3`

substitute C=3 in 9iv) we have

B-12=-10

B=-10+12

B=2

substitute C=3 in (ii)

2A-3=-1

2A=-1+3

2A=2

A=1

**Thus answer is**

**A=1, B=2, and C=3.**